Simulation studies on different types of plasma devices - Lee, Henry Victorio Jr.; Ramos, Henry J. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2010)
The study presents the results from the computer simulation of three different plasma systems. The objective of this study is to gain useful insights on the plasma behaviour within different types of plasma devices.The three devices are namely: a Plasma Sputter Type Negative Ion Source (PSTNIS), a microwave Induced Plasma Source and a Magnetized Sheet Plasma Source. A Particle-in-cell (PIC) method is the general method used in the plasma simulations. The PICmethod is modifie to suit the different plasma conditions for each system.When the simulation of collisions is required, he Particle-in-Cell with Monte Carlo Collisions (PIC-MCC) model is used. The simulation results for each system are compared and related with existing experimental data. The simulation results on the PSTNIS show optimum combinations of Einzel len and accelerator voltages for ion beam focusing and acceleration. Compared to past research data, the optimum Einzel lens voltage found in the simulation matched the experimentally determined optimum Einzel lens voltage. For the microwave plasma simulation, plasma behaviour from experimental plasma images also coincides with the simulation results. In the case of the magnetized sheet plasma source, it is found that the parmeters considered in the simulation are insufficient in supporting existing research findings. As such, further simulation studies are proposed. Overall, the simulation is successful in modeling ion beams in the PSTNIS and electron behaviour in a microwave plasma source, but is found to be insufficient for the case of a magnetized sheet plasma source.
Thesis (M.S.-Physics)--University of the Philippines Diliman
Keywords: Plasma devices